An Act to Amend Chapter 35 of Title 44, United States Code, for the Purpose of Facilitating Compliance by Small Business Concerns with Certain Federal Paperwork Requirements, to Establish a Task Force to Examine Information Collection and Dissemination, and for Other Purposes. (2002)
Summary goes here